A novel mRNA-based multi-epitope vaccine for rabies virus computationally designed via reverse vaccinology and immunoinformatics - Wafa Tombari; Oussema Khamessi; Houcemeddine Othman; Ouafa Kallala; Rihab Mahjoub; Kais Ghedira; Abdelhalim Trabelsi (Scientific Reports)
Abstract The current research investigated the development of a multi-epitope mRNA vaccine against the rabies virus on the basis of viral proteomes via the use of bioinformatic tools and reverse vaccinology. The aim of this study was to address the limitations of the currently available rabies vaccine by eliciting strong and long-lasting humoral and cellular immune responses. The cytotoxic T lymphocytes (CTLs), helper T lymphocytes (HTLs), and linear B-cell epitopes (LBLs) were mapped and prioritized from four top-ranking vaccine targets (nucleoprotein, phosphoprotein, matrix, and glycoprotein) that were highly antigenic, nonallergenic, nontoxic, and nonhuman homologs. The selected epitopes exhibited strong binding affinity to high-frequency HLA alleles, as evidenced by highly negative ΔG values and low dissociation constants, predicting efficient T-cell recognition and broad population coverage (96.01% globally). A single mRNA construct encompassing 21 shortlisted epitopes (four CTL, four HTL, and thirteen LBL epitopes) was designed with appropriate linkers and the immunostimulatory 50 S ribosomal protein L7/L12 adjuvant. Physicochemical analysis revealed stable, soluble, and hydrophobic properties, with an overall Ramachandran score of 93.2%, an ERRAT quality factor of 94.724%, and a Z score of -5.39. Additionally, molecular docking and normal mode analysis demonstrated the strong binding affinity of the vaccine construct-TLR-4 complex, with a minimum energy of -1655.0 kcal/mol, which was maintained by 23 hydrogen bonds and 2 salt bridge interactions, indicating significant structural stability and stiffness. The structural integrity and stable interaction of the complex were validated through 200 ns molecular dynamics simulations, as evidenced by stable RMSD and radius of gyration values, minimal fluctuations in RMSF, consistent solvent-accessible surface area (SASA), and well-defined conformational transitions observed in principal component analysis (PCA). In silico immune simulation revealed the capacity of the vaccine to stimulate the release of high levels of immunoglobulin, TH, and TC and the release of cytokines. It also has the ability to produce long-lasting memory cells, induce macrophage activity, and promote natural killer cell and neutrophil production. Moreover, further validation, including codon optimization and mRNA secondary structure prediction, confirmed the stable structure and high level of expression in the host. Overall, this study proposed a promising multi-epitope-based mRNA vaccine as an innovative therapeutic candidate against rabies. However, experimental validations are needed with systemic animal studies.